Salivary Biomarkers of Oxidative Stress in Methamphetamine Users: A Case-Control Study - Saeed Afzali; Fatemeh Fadaei; Akram Oftadeh; Akram Ranjbar (Novelty in Clinical Medicine, 2022)
Background: Methamphetamine abuse, a potent and highly addictive stimulant, remains an extremely serious problem in many societies. It seems that methamphetamine consumption increases free radicals and causes oxidative stress in the body, which has many side effects.Objectives: The aim of this study was to evaluate the level of oxidative stress biomarkers in the saliva of methamphetamine users compared with healthy individuals.Methods: In this case-control study, 36 methamphetamine users and 27 healthy individuals referred to Farshchian Hospital in Hamadan, Iran with similar demographic data were included. The written informed consent form was signed by all participants. Two ml of saliva was collected from the study subjects. The supernatant was used for the analysis of catalase activity, total thiol molecules, and total antioxidant capacity.Results: No statistical difference was observed in the demographic data between case and control groups. The mean of total antioxidant capacity in methamphetamine users (0.10±0.01) was significantly lower than in healthy individuals (0.64±0.12 μmol/ml) (P<0.001). The catalase activity and thiol groups in saliva did not show a significant difference between the two groups.Conclusion: According to the results, it seems that the use of amphetamine compounds acutely and chronically induces oxidative stress and increased oxidants in these individuals.